FAMILY PARTICIPATION MODEL WITH CHILDREN WITH DISABILITIES IN REALISING AN INCLUSIVE SOCIETY - Astutik, Juli; Suprapto, Budi; Abidin, Zaenal; Yahaya, Mohd Haizzan (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2023)
Abstract. This research aims to find a model of family participation with children with disabilities in realising an inclusive society in Ngawonggo Village, Tajinan District, Malang Regency. This research was conducted with a qualitative approach of the descriptive type. The research subjects were determined by the purposive method. Data collection techniques were carried out by observation and interview. Data analysis was conducted using the interactive model (Milles and Huberman).  The results showed that the forms of family participation with children with disabilities include: 1) Participation in decision-making, 2).  Participation in implementation, 3) Participation in benefits, and 4) Participation in evaluation. with socialisation programs, family parenting and therapy, can create an inclusive society, such as: 1)  Religious and community leaders understand the importance of supporting the growth and development of children with disabilities, 2) The community treats children with disabilities as normal, 3) Children with disabilities can play and learn with normal peers, 4) There is support from the local government for children with disabilities through the allocation of the Village Fund Budget, 5) Parents with children with disabilities have gradually opened up and provided public access to their children. Keywords: Family Participation, Children with Disabilities, Inclusive Society. Abstrak. Penelitian ini bertujuan untuk menemukan model partisipasi keluarga dengan anak penyandang disabilitas dalam mewujudkan masyarakat inklusi di Desa Ngawonggo, Kecamatan Tajinan, Kabupaten Malang. Penelitian ini dilakukan dengan pendekatan kualitatif dengan tipe deskriptif. Subjek penelitian ditentukan dengan metode purposif. Teknik pengumpulan data dilakukan dengan observasi dan wawancara. Analisis data dilakukan dengan menggunakan model interaktif (Milles dan Huberman).  Hasil penelitian menunjukkan bahwa bentuk-bentuk partisipasi keluarga dengan ABK antara lain: 1) Partisipasi dalam pengambilan keputusan, 2).  Partisipasi dalam pelaksanaan, 3) Partisipasi dalam manfaat, dan 4) Partisipasi dalam evaluasi. Dengan adanya program sosialisasi, pola asuh keluarga dan terapi, dapat menciptakan masyarakat yang inklusif, seperti: 1) Tokoh agama dan tokoh masyarakat memahami pentingnya mendukung tumbuh kembang ABK, 2) Masyarakat memperlakukan ABK sama seperti anak normal lainnya, 3) ABK dapat bermain dan belajar bersama teman sebaya yang normal, 4) Adanya dukungan dari pemerintah daerah terhadap ABK melalui pengalokasian Anggaran Dana Desa, 5) Orang tua yang memiliki ABK berangsur-angsur membuka diri dan memberikan akses publik terhadap anaknya. Kata Kunci: Partisipasi keluarga, ABK, Masyarakat inklusif.